Sustainable transportation and smart logistics : decision-making models and solutions - Faulin, Javier; Grasman, Scott E. (Scott Erwin); Juan, Angel A., 1972-; Hirsch, Patrick (Elsevier, 2019)
Sustainable Transportation and Smart Logistics: Decision-Making Models and Solutions provides deterministic and probabilistic models for transportation logistics problem-solving and decision-making. The book presents an overview of the intersections between sustainability, transportation, and logistics, and delves into the current problems associated with the implementation of sustainable transportation and smart logistics in urban settings. It also offers models for addressing complex structural problems and procedures for estimating transportation externalities such as environmental and social impacts, both in industrial and government arenas, as well as decision-making models from operational, tactical, and strategic management perspectives. Sustainable Transportation and Smart Logistics also covers best practices for practical corporate policy implementation, making it a comprehensive and vital resource for researchers, graduate students, practitioners, and policy makers in transportation, logistics, urban planning, economics, engineering, and environmental science.